Comparative Transcriptome Profiling Reveals Insights Into the Mechanisms Related to Explosive Growth of Alexandrium pacificum - Liu, Yuan; Zhu, Zhimei; Qi, Juan; Sui, Zhenghong; Shang, Erlei; Zhang, Shu; Niaz, Zeeshan (Frontiers in Marine Science, 2021)
Alexandrium pacificum is an organism that has an important impact on the aquaculture industry and human health. In this study, the digital gene expression approach was used to conduct a comparative analysis of differentially expressed genes (DEGs) that influence the explosive growth of A. pacificum following five treatment conditions: normal culture (C), high phosphorus and manganese (M), high irradiance (G), low phosphorus (P) and low nitrogen (N). Compared with the C conditions, a total of 265, 320, 185 and 150 DEGs were detected in the M, G, P and N treatment groups, respectively. Clustering analysis suggested that A. pacificum acclimated to explosive growth using similar mechanisms in the M and G conditions. Analysis of DEGs showed that upregulation of genes associated with the pentose phosphate pathway and photosynthesis may contribute to explosive growth. Unigenes involved in the cell cycle were also found to be upregulated to promote cell division. The DEGs identified in this study may allow for the elucidation of molecular mechanisms responsible for the explosive growth of A. pacificum.